Satisfaction of Family Physician Plan: Viewpoint of Physicians and Health Service Consumers in Kerman, Southeast of Iran - Ahmadi, Batoul; Pourebrahimi, Mohammad Hossein; Ram Bejandi, Malihe; Ram Bejandi, Malihe; Sadeghi, Ahmad; Khammarnia, Mohammad; Siavashi, Elham (Galen Medical Journal, 2015)
Background: Family Physician plan is known as one of the most appropriate strategies to implement rural health insurance program in the form of referral system in Iran. This study aims to determine the satisfaction of family physicians and service consumers and its causes of dissatisfaction in the South of Iran. Materials and Methods: This cross-sectional study was performed in Kerman Health Network. Nineteen family physicians and 370 service consumers were selected using stratified random sampling. Data was gathered using two standardized questionnaires. Frequency tables, frequency percentage, mean graphs, Z and Freedman statistical tests were used to analyze the data. Results: Mean scores of physicians’ satisfaction were 9.10 and 4.12 in staff performance and payment system, respectively. Service consumers were satisfaction of physician delivery care (7.25), and para-medical (3.61). Moreover, most physicians were interested in per capita (31/6%). Conclusion: Family physician and health service consumers are highly satisfied. Satisfaction is an important factor for ensuring service quality and any ignorance in this regard can reduce the quantity and quality of delivered care. Physicians are recommended to respect their consumers and consider their waiting time. Meanwhile, health system managers should promote physicians’ payment. [GMJ.2015;4(2):96-102]